The American century - Johnston, Robert D., author. Link
1 online resource
Keywords: The new edition of this classic text on modern U.S. history seamlessly blends political, social, cultural, intellectual, and economic themes into an authoritative and readable account of America's national story since the 1890s. Written by four highly respected scholars, this book has been fully updated with new coverage of the Trump and Biden presidencies, the culture wars, deep political polarization, and the crisis of democracy. The text's most distinctive quality is its close attention to both history within the United States and the relationships the country has forged with the rest of the world. The eighth edition remains engaging and approachable while continuing to include the most recent scholarship. Each chapter contains a special feature section devoted to cultural topics including the arts and architecture, sports and recreation, technology, and education. Web links to additional online resources accompany each feature, offering complementary learning opportunities to students. While carefully attending to the complexity of history, The American Century traces the long roots of some of the most pressing current issues in the United States and continues to be a compelling resource for students of recent American history.